Peningkatan Daya Tangkap Kognitif Anak melalui Metode Pembelajaran Permainan Puzzle di Rumah Ngaji Anak Syamilul Qur`An - Isnaeni, Fil; Budiman, Septian Arief; Hadi, Sofyan (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
This community service activity is one of the academic obligations that must be carried out in each semester with the aim of providing guidance and educational services to the community, this semester's community service activities raise the theme of creativity and children's cognitive comprehension, Creativity has a very important role for development child. Creativity is the ability to generate new ideas, see the world in unique ways, and explore possibilities. Through creativity, children can develop a range of invaluable intellectual, emotional and social skills. The methods used in this activity include: motivation and inspiration with stories, exploration of creativity through games, and appreciation, while the object of this activity is the students of the Syamilul Qur'an recitation house for children. This activity is expected to increase the spirit of learning religion in children and increase children's cognitive comprehension and stimulate children's creativity and the results of this activity for lecturers can increase awareness in the field of education in accordance with the fields of knowledge mastered.